2020
DOI: 10.20944/preprints202007.0130.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Impair Intestinal Barrier Function during Experimental Colitis

Abstract: Aberrant neutrophil extracellular trap (NET) formation and the loss of barrier integrity in inflamed intestinal tissues have long been associated with inflammatory bowel disease (IBD). However, whether NETs alter intestinal epithelium permeability during colitis remains elusive. Here, we demonstrated that NETs promote the breakdown in intestinal barrier function for the pathogenesis of intestinal inflammation in mouse models of colitis. NETs were abundant in the colon of mice with colitis experimentall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 42 , 43 NETs are found to accumulate in inflamed intestinal mucosa from patients with active UC and sustain inflammatory signals. 44 Recent studies also demonstrated the pathological role of NETs in inflamed mucosa, such as impairing intestinal barrier function, 45 and inducing intestinal damage and thrombotic tendency. 24 PMA is an artificial stimuli to profoundly induce neutrophil production of extracellular traps.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 NETs are found to accumulate in inflamed intestinal mucosa from patients with active UC and sustain inflammatory signals. 44 Recent studies also demonstrated the pathological role of NETs in inflamed mucosa, such as impairing intestinal barrier function, 45 and inducing intestinal damage and thrombotic tendency. 24 PMA is an artificial stimuli to profoundly induce neutrophil production of extracellular traps.…”
Section: Discussionmentioning
confidence: 99%
“…NETs have been implicated in many gastrointestinal diseases including inflammatory bowel diseases (IBDs) [ 39 , 40 , 41 ], liver disease [ 35 ], and acute pancreatitis [ 42 , 43 , 44 ]. A chronic abiding repetitive event of inflammation in intestinal epithelium is portrayed as IBD [ 39 ].…”
Section: Nets In Gastrointestinal Inflammationmentioning
confidence: 99%
“…A chronic abiding repetitive event of inflammation in intestinal epithelium is portrayed as IBD [ 39 ]. Aberrant NET accumulation and the deterioration of inflamed intestinal barrier integrity can be correlated with IBD [ 39 ], as in ulcerative colitis (UC) [ 40 ]. Neutrophils and NET-associated molecules are found in abundance in both colonic biopsies of UC [ 45 , 46 ] and Crohn’s disease (CD) [ 41 ], which indicate intestinal inflammatory aggravation, epithelial exasperation, and elevated thrombotic impulse [ 47 ].…”
Section: Nets In Gastrointestinal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation